Motivational factors towards consuming herbal-based nutraceutical products among Malaysians - Kamarulzaman, Nitty Hirawaty; Said, Ilyas (Faculty of Computer Science and Information Technology, Universiti Putra Malaysia, 2015)
The Ministry of Health Malaysia (MOH) reported an alarming increase in prevalence of overweight and obesity, diet-related diseases such as type 2 diabetes, cardiovascular disease, hypertension and certain forms of cancer in the last few years. As part of their health concern, Malaysian consumers were reported to spend between RM50 to RM500 per month on health supplements, both pharmaceutical and traditional. The Economic Planning Unit (EPU) Malaysia estimated the market value for herbal products will rise from RM7 billion to RM29 billion in 2020. All these figures highlight a trend in which Malaysian consumption of herbal-based nutraceutical products had been increased. Thus, it is important to investigate what are the factors that motivated Malaysian consumers to purchase herbal-based nutraceutical products? This paper seeks to investigate the motivational factors of Malaysian towards consuming herbal-based nutraceutical products. The result revealed that brand, health problems, recommendation from medical expert, advertisement on electronic and social media and the availability of the products in Malaysia were the motivational factors towards consuming herbal-based nutraceutical products. It is recommended that relevant advertisements or campaigns could further increase consumers to purchase the products.